Nekaj novih algoritmov za računalniško podprto načrtovanje montaže - Kunica, Zoran (Strojniški vestnik, 2003)
The paper depicts some of the improved and newly implemented algorithms of the computer aided design (CAD) based system for the plan generation of automatic assembly (GPAS), relating to definitions of assembly sequence and paths, space structuring (layout) of the assembly process for bench assembly product orientation, connectivity, and treatment of identical parts in a product. In the approach, the parts of which are presented in the paper, the mechanical product to be assembled is, initially, a CAD-modelled assembled product. After this, the planing elements, such as the assembly sequence, the assembly paths and the parts positions of the disassembled product are defined, providing the basis for assembly-device design and assembly execution.
Keywords: montaža; avtomatizacija montaže; planiranje montaže; CAD-CAE-CAM; avtomatizacija